Neurosurgical Post‐Operative Wound Infections: A retrospective study on surgical site infections for quality improvement. Issue 4 (21st April 2020) - Fiani, Brian; Cathel, Alessandra; Sarhadi, Kasra J.; Cohen, Jordan; Siddiqi, Javed
Abstract: Despite efforts to maintain a meticulous aseptic environment, wound infection is one of the most common complications following surgery and may be related to dehiscence, haemorrhage, infection, and/or poor surgical technique. With the appearance of new wound closure techniques and suture materials, we felt compelled to perform a retrospective study on our institution's neurosurgical population to determine how our institution compared to others in terms of incidence of surgical site infection (SSI). A retrospective analysis was performed at our single institution for all patients that had cranial or spine surgery by a neurosurgeon for the past 15 years. The data were extracted via Crimson Continuum of Care software program and analysed using χ 2 and relative risk. The data retrieval software program collected a total of 1184 cranial and spinal surgeries. Of these 1184 cases, 12 resulted in post‐operative wound infections. Using these collected values, we compared the results with published values in the literature. Prior studies have shown that up to 33% of surgical cases have post‐operative infections. Using this reported value in comparison with our data, χ 2 testing equals 547.893 with 1 df, P = .0001 (confidence interval = 0.05), which demonstrated statistical significance when compared with surgical literature. The results from this retrospective analysis demonstrated that the rate of neurosurgical post‐operative SSI falls within the range consistent with the literature, which has shown rates of infection from <1% up to 15% depending on the type of surgery, surgical technique, and patient characteristics. SSIs can be an unfortunate and costly post‐operative complication. Risks factors in the past have been studied, but introspection by each institution is an important metric to ensure accountability and provide optimal patient care in comparison with established data and guidelines. No deviation from current techniques is deemed necessary at our institution based on the results.